Interaction of N-acetylneyraminic acid with surface of silica with fructose in aqueous solution - Ushakova, L.M.; Demianenko, E.M.; Terets, M.I.; Lobanov, V.V.; Kartel, N.T. (Physics and Chemistry of Solid State, 2021)
Quantum chemical simulation of the adsorption of N acetylneuraminic acid (NANA) on the surface of silica with the participation of the fructose molecule by the method of density functional theory B3LYP, 6-31G (d, p) was done. The influence of the solvent was taken into account in the supermolecular and continuum approximations, and a cluster approach was used for the adsorption complexes. NANA adsorption of the hydrated silica surface was considered as a process of replacement of water molecules on the silica surface by adsorbate molecules. Two schemes of influence of fructose molecule on NANA adsorption are considered. According to the first scheme, the hydrated NANA molecule interacts with the hydrated silicon-fructose adsorption complex. According to the second scheme, the cluster of hydrated silica interacts with the hydrated NANA-fructose complex. The energy of intermolecular interaction according to the scheme 1 is -9.2 kJ / mol, which is significantly lower compared to the same value with the participation of glucose or sucrose (-20.5 and -86.2 kJ / mol). Scheme 2 proved to be a thermodynamically unfavorable process, as its energy effect is +6.9 kJ / mol, in contrast to similar processes for glucose (-21.8) and sucrose (-87.7 kJ / mol). This confirms the experimental fact of the interaction of substances in a mixture of NANA with carbohydrates in relation to the interaction with silica in comparison with the interaction of substances with silica separately.